Pengaruh Aminoethoxyvinylglycine (Avg), Plastic Wrapping Dan Suhu Simpan Terhadap Masa Simpan Dan Mutu Buah Jambu Biji (Psidium Guajava L.) ‘Mutiara’ - Soesiladi E. Widodo; Kuswanta F. Hidayat; Zulferiyenni Zulferiyenni; Sherly I. Annisa (Politeknik Negeri Lampung., 2016)
The research was aimmed at studying the effects of (1) single application AVGs,plastic wrappings, and storage temperatures, (2) interactions among AVGs andplastic wrappings, AVGs and storage temperatures, and plastic wrappings andstorage temperatures, and (3) interactions among AVGs, plastic wrappings, andstorage temperatures in extending fruit self-life and maintain qualities of‘Mutiara’guava fruits. The research was arranged in a completely randomized designin 2 x 2 x 2 factorial with three replications. The first factor was AVGs (with 1,25ppm and without AVG), the second factor was plastic wrappings (without and withone layer of plastic wrapping), and the third factor was storage temperature (a coldtemperature of 21, 53 ºC and a room temprature of 26,57 ºC). The result showed that(1) the application of AVG 1,25 ppm did not significantly affect fruit self-life, fruitfirmness, fruit weight loss, ºBrix, acid contens, and sweetness of ‘Mutiara’guava’fruits, (2) storage at cold temprature of 21, 53 ºC did not significantly affect fruit self-life, fruit firmness, fruit weight loss, ºBrix, acid contens, and sweetness of‘Mutiara’guava’ fruits, (3) the application of plastic wrapping was able to extend fruitself-life by 17 days longer than without plastic wrapping and supressed fruit weightloss of ‘Mutiara’guava, but accelerated softening and not able to maintain ºBrix, andalso did not significantly affect acid contens, and sweetness of ‘Mutiara’guava fruits,(4) there were no interaction effects among AVGs with plastic wrappings, AVGs withcold tempratures, and plastic wrappings with cold tempratures on self-life, fruitfirmness, fruit weight loss, ºBrix, acid contens, and sweetness of ‘Mutiara’guavafruits, and (5) there were no interaction effects among AVGs, plastic wrappings, andcold temperatures on fruit self-life, fruit firmness, fruit weight loss, ºBrix, acidcontens, and sweetness of ‘Mutiara’ guava fruits.